Implementasi Fault Tolerant System dengan N-modular Hardware Redundancy - Khurinika Cahyaning Susanty; Wijaya Kurniawan; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Fault tolerant is needed because many systems are in conditions such critical systems, prone to damage environment, complex designs, and systems with variety users. The survey results of IT company said 99% of 400 respondents had experienced system failure caused by hardware damage resulting in data loss. To overcome this problem, a fault tolerant system was implemented on the hardware part (hardware redundancy) using N-Modular Redundancy (NMR) method that was applied on intensity and temperature reader system. NMR work by duplicate hardware as N that works together and get the same input and then the output results are determined by voting logic using majority vote. The object of implementation is intensity sensor BH1750 and temperature sensor LM35 as input, Arduino Uno as a sensor reader and voter, and the output will be displayed in the Arduino IDE serial monitor. The redundant hardware is sensor reader, Arduino Uno. The test results showed that the system more reliable because even though one of the redundant modules was damaged, the system still operate properly from the other redundant modules that running normally. The analysis before and after the application of the TMR method, reliability system increased by 9.2% from 83.51% to 92.7%.